Comparison of aberrant behavior profiles across different severity levels of autism symptoms among Thai children aged 2-9 years with autistic spectrum disorder - Suvannang, Prinne; Nopparat, Chutikorn; Thichanpiang, Peeradech; Kunwittaya, Sarun; Kleebpung, Nonthasruang; Kaunnil, Anuchart; Permpoonputtana, Kannika (Journal of Associated Medical Sciences, 2023)
Background: The incidence of autism spectrum disorder (ASD) has been increasing steadily, thus posing a substantial public health concern in Thailand and globally. Individuals with ASD, who frequently experience challenges related to their behavior and emotions, have neurodevelopmental disorders. The Aberrant Behavior Checklist (ABC) represents one available tool for addressing these issues. Objectives: This study aimed to explore and compare aberrant behavior profiles across different severity levels of autism among Thai children aged 2-9 years with ASD. Materials and methods: The participants comprised 71 parents and young children with ASD, recruited online, particularly from an online Facebook community of parents from diverse regions of Thailand. A convenience sampling method was employed for selecting the participants. The research tools consisted of 3 parts for collecting data. Demographic data were used for collecting such information about the participants. A Thai version of the Autism Treatment Evaluation Checklist (ThaiATEC) was utilized to measure autism symptom severity, and the Aberrant Behavior Checklist-Community (ABC-C) Thai Version was used for evaluating behavioral problems from caregiver administration. Results: A total of 71 ASD participants were identified, of which 5, 15, and 51 displayed mild, moderate, and severe symptoms of ASD, respectively. The mean scores of aberrant behaviors, as assessed by the ABC-C Thai version, showed an increase across all four subscales and the total score in response to the severity levels of ASD symptoms. The study findings, including reported correlations between aberrant behaviors and severity levels of autism symptoms, revealed predominantly high correlation coefficients (rs ranging from 0.27 to 0.93). Furthermore, a positive correlation was identified between the four subscales of the Thai-ATEC assessment and the five subscales of the ABC-C Thai version, highlighting their interrelated nature. For more detailed analysis, the ASD participants were categorized into two groups: a “mild-moderate” group consisting of 20 participants and a “severe” group comprising 51 participants. Subsequently, a comparison was made between the mean scores of the ABC-C subscales and total scores. The results of this comparison demonstrated significant distinction in all five subscales and the total score of the ABC-C Thai version between the “mild-moderate” and “severe” groups of ASD participants. These findings shed light on the notable differences in aberrant behavior profiles between individuals with varying levels of autism symptom severity. Conclusion: The aberrant behaviors increased in response to severe symptoms of ASD. This might be useful for clinical purposes, and assessing aberrant behaviors may help understand behavioral problems and severity levels of ASD and tailoring occupational therapy interventions.